ESG analysis of companies included in the RESPECT Index based on Thomson Reuters EIKON database - Sikacz, Hanna; Wołczek, Przemysław (Research Papers of Wrocław University of Economics, 2018)
The purpose of this paper is to present the results of an ESG analysis of companies from the RESPECT Index. The results of the analysis prompt the authors to formulate a postulate that ESG ratings of companies should be taken into account in the subsequent editions of the RESPECT Index. Thomson Reuters EIKON database can be used to assess the manner of managing the ESG factors by companies. It is also proposed that the stakeholders and, in particular, investors that pay attention to ESG ratings of companies, should take into account this database when analysing potential investments
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 520; s. 115-127
Keywords: ESG factors; ESG analysis; RESPECT index; Thomson Reuters EIKON